Creativity In Sasando Violin Music Learning In Kupang East Nusa Tenggara Timur - Margareta Sofyana Irma Kaet (Edumaspul: Jurnal Pendidikan, 2023)
The background of this research is the learning activities of students from the Edon Sasando Kupang studio, who have talent and creativity in the field of Sasando Biola music. This research was carried out with the aim of developing talents, interests, and creativity in studio students through lecture, demonstration and drill methods. This type of research uses descriptive qualitative with twelve research subjects, consisting of five juniors and seven seniors. Where the data obtained directly by the researcher there were four people in the junior class who were less creative, and independent, during the learning process in class, while the seven people in the senior class looked more creative, independent and effective. The results of the study as a whole show that firstly students become aware of playing Sasando Biola, secondly there is creativity in Sasando Biola accompaniment with a combination of several electric musical instruments which already have developments in the initial melody, rhythm and bass of the song, thirdly it can support the development of talents and abilities the creativity of studio students in participating in various artistic activities, as part of an attitude of appreciation and preservation of the art of Sasando music in society.